2017
DOI: 10.1159/000457938
|View full text |Cite
|
Sign up to set email alerts
|

The Novel Long Noncoding RNA TUSC7 Inhibits Proliferation by Sponging MiR-211 in Colorectal Cancer

Abstract: Background/Aims: The novel long noncoding RNA (lncRNA) tumor suppressor candidate 7 (TUSC7) has been reported as a potential tumor suppressor, while the functional role of TUSC7 is still unknown in colorectal cancer (CRC). Here, we characterized TUSC7 expression profile in CRC patients and investigated its biological function and potential molecular mechanism. Methods: RNA isolation, qRT-PCR, cell counter kit-8 assay, cell cycle assay, EdU assay, and western blot were performed. Statistical analyses were perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
80
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(83 citation statements)
references
References 29 publications
3
80
0
Order By: Relevance
“…Currently, the newly uncovered lncRNAs, emerged as important factors in cellular processes and human diseases, have been attracting more and more attentions of researchers. For example, novel lncRNA TUSC7 was identified dysregulated in colorectal cancer and regulating cell proliferation through sponging miR-211 [28]. And lncRNA TRPM2-AS was demonstrated as novel prognostic marker and therapeutic target in prostate cancer [29].…”
Section: Discussionmentioning
confidence: 99%
“…Currently, the newly uncovered lncRNAs, emerged as important factors in cellular processes and human diseases, have been attracting more and more attentions of researchers. For example, novel lncRNA TUSC7 was identified dysregulated in colorectal cancer and regulating cell proliferation through sponging miR-211 [28]. And lncRNA TRPM2-AS was demonstrated as novel prognostic marker and therapeutic target in prostate cancer [29].…”
Section: Discussionmentioning
confidence: 99%
“…lncRNAs have been reported to be involved in a variety of biological processes, including tumorigenesis through regulating oncogenes or tumor suppressors at several levels (3)(4)(5)(6)(7)(8)(9)(10)(11)(12). For example, Xia et al (13) demonstrated that long noncoding RNA papillary thyroid carcinoma susceptibility candidate 3 (PTCSC3) inhibited proliferation and invasion of glioma cells by suppressing the Wnt/β-catenin signaling pathway.…”
Section: Introductionmentioning
confidence: 99%
“…To better understand and identify efficient new biomarkers of COAD, we are studying the mechanisms of COAD. Recent studies have shown that lncRNAs play vital roles in the development of cancer [2,3,[18][19][20][21], but there have been very few studies that focused on the profiles of lncRNAs in CRC. lncRNAs mRNA targets HOTAIR REV3L, INO80D, PHIP, AGO3, TAOK1, ATM, GPATCH2L, RC3H1, SHPRH, RICTOR, MAP3K2, ATAD2B, RIC1, PIKFYVE, WDPCP, USP34, PHC3, MIR133A1HG, BRWD1, ZBTB37 LINC00355 ATM, REV3L, GPATCH2L, RICTOR, SHPRH, PHIP, AGO3, WDPCP, INO80D, RIC1, RC3H1, TAOK1, USP34, ATAD2B, MFSD4B, FAM217A, PIKFYVE, ZBTB37, NBEAL1, GDAP2 TSSC1-IT1 SHPRH, INO80D, LRRTM2, TNRC6B, GPATCH2L, PHC3, GPR52, RC3H1, AGO3, ZBTB20, REV3L, NBEAL1, RNF169, TAS2R19, MFSD4B, IFNK, CLDN20, RIC1, FBXL13, MATR3 KCNQ1OT1 SHPRH, INO80D, AGO3, LRRTM2, RC3H1, MIR133A1HG, GPATCH2L, REV3L, MATR3, ZBTB20, PHC3, GPR52, GDAP2, POU5F2, MFSD4B, NBEAL1, TAS2R19, ATM, C1orf195, AIRN LncRNAs have sophisticated functions through diverse pathways, and the ceRNA hypothesis makes the relationship between lncRNAs, miRNAs, and mRNAs more complicated.…”
Section: Discussionmentioning
confidence: 99%